Multicellular Human Gastric Cancer Spheroids Mimic the Glycosylation Phenotype of Gastric Carcinomas - Balmaña, M (2018)
Cellular glycosylation plays a pivotal role in several molecular mechanisms controlling cell⁻cell recognition, communication, and adhesion. Thus, aberrant glycosylation has a major impact on the acquisition of malignant features in the tumor progression of patients. To mimic these in vivo features, an innovative high-throughput 3D spheroid culture methodology has been developed for gastric cancer cells. The assessment of cancer cell spheroids' physical characteristics, such as size, morphology and solidity, as well as the impact of glycosylation inhibitors on spheroid formation was performed applying automated image analysis. A detailed evaluation of key glycans and glycoproteins displayed by the gastric cancer spheroids and their counterpart cells cultured under conventional 2D conditions was performed. Our results show that, by applying 3D cell culture approaches, the model cell lines represented the differentiation features observed in the original tumors and the cellular glycocalix underwent striking changes, displaying increased expression of cancer-associated glycan antigens and mucin MUC1, ultimately better simulating the glycosylation phenotype of the gastric tumor.